Contact tracing performance during the Ebola virus disease outbreak in Kenema district, Sierra Leone. (26th May 2017) - Senga, Mikiko; Koi, Alpha; Moses, Lina; Wauquier, Nadia; Barboza, Philippe; Fernandez-Garcia, Maria Dolores; Engedashet, Etsub; Kuti-George, Fredson; Mitiku, Aychiluhim Damtew; Vandi, Mohamed; Kargbo, David; Formenty, Pierre; et al.
Abstract : Contact tracing in an Ebola virus disease (EVD) outbreak is the process of identifying individuals who may have been exposed to infected persons with the virus, followed by monitoring for 21 days (the maximum incubation period) from the date of the most recent exposure. The goal is to achieve early detection and isolation of any new cases in order to prevent further transmission. We performed a retrospective data analysis of 261 probable and confirmed EVD cases in the national EVD database and 2525 contacts in the Contact Line Lists in Kenema district, Sierra Leone between 27 April and 4 September 2014 to assess the performance of contact tracing during the initial stage of the outbreak. The completion rate of the 21-day monitoring period was 89% among the 2525 contacts. However, only 44% of the EVD cases had contacts registered in the Contact Line List and 6% of probable or confirmed cases had previously been identified as contacts. Touching the body fluids of the case and having direct physical contact with the body of the case conferred a 9- and 20-fold increased risk of EVD status, respectively. Our findings indicate that incompleteness of contact tracing led to considerable unmonitored transmission in the early months of the epidemic. To improve the performance of early outbreak contact tracing in resource poor settings, our results suggest the need for prioritized contact tracing after careful risk assessment and better alignment of Contact Line Listing with case ascertainment and investigation. This article is part of the themed issue 'The 2013–2016 West African Ebola epidemic: data, decision-making and disease control'.